2017
DOI: 10.1038/srep44922
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented simultaneous enhancement in damage tolerance and fatigue resistance of zirconia/Ta composites

Abstract: Dense (>98 th%) and homogeneous ceramic/metal composites were obtained by spark plasma sintering (SPS) using ZrO2 and lamellar metallic powders of tantalum or niobium (20 vol.%) as starting materials. The present study has demonstrated the unique and unpredicted simultaneous enhancement in toughness and strength with very high flaw tolerance of zirconia/Ta composites. In addition to their excellent static mechanical properties, these composites also have exceptional resistance to fatigue loading. It has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 54 publications
(70 reference statements)
0
34
0
1
Order By: Relevance
“…Recently, Smirnov et al have developed a new zirconium dioxide–tantalum (ZrO 2 –Ta) ceramic–metal composite, or biocermet, with an unprecedented combination of high toughness, strength, damage tolerance, and fatigue resistance. The field of modern dentistry could take advantage of this biocermet's mechanical properties, using it for screw‐retained restorations, for example, to extend the lifetime of dental implants.…”
Section: Mechanical Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Smirnov et al have developed a new zirconium dioxide–tantalum (ZrO 2 –Ta) ceramic–metal composite, or biocermet, with an unprecedented combination of high toughness, strength, damage tolerance, and fatigue resistance. The field of modern dentistry could take advantage of this biocermet's mechanical properties, using it for screw‐retained restorations, for example, to extend the lifetime of dental implants.…”
Section: Mechanical Concernsmentioning
confidence: 99%
“…Gibbs et al 74 measured the occlusal force produced during chewing and swallowing for humans under normal conditions and found that the average force applied at cusp is calculated to be 242 N. The fatigue limit was determined as the stress at which no failure occurred in two million cycles (N f = 2 × 10 6 cycles), which represents 4 years of simulated function if the daily masticatory number per day is estimated to be 1400 cycles. 74 Recently, Smirnov et al 75,76 have developed a new zirconium dioxide-tantalum (ZrO 2 -Ta) ceramic-metal composite, or biocermet, with an unprecedented combination of high toughness, strength, damage tolerance, and fatigue resistance. The field of modern dentistry could take advantage of this biocermet's mechanical properties, using it for screw-retained restorations, for example, to extend the lifetime of dental implants.…”
Section: Mechanical Concernsmentioning
confidence: 99%
“…Thanks to these properties, ceramics are used in multifunctional applications such as biomedical engineering, electronics, aerospace, chemical industry, and machinery [2]. Note that the advantage of ceramics over other materials is the ability to obtain predetermined characteristics by changing the raw materials composition and the production technology [3][4][5][6][7][8]. Commonly, raw materials are composed by mixtures of ceramic powders with or without binders and additives, and these mixtures are used to form green bodies with desired simple shape by different forming methods as dry pressing, slip casting, injection molding, gel casting, tape casting, extrusion and others [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that insufficient fracture toughness becomes a reason for microcracks formation and propagation on the surface of ceramic cutting tools [1][2][3]. One of the most effective methods to increase reliability of the ceramic tools is to deposit thin-film wearresistant coatings by physical vapor deposition (PVD) technique [4,5].…”
Section: Introductionmentioning
confidence: 99%